Interaction between sex and one-hour post-load glucose on metabolic syndrome and its components among Chinese people at high risk of diabetes - Xin Chai; Juan Zhang; Yachen Wang; Di Li; Dongli Zhu; Kaipeng Liang; Chunyu Yang; Jinping Wang; Qiuhong Gong; Zhiwei Yang; Ruitai Shao (Diabetology & Metabolic Syndrome)
Abstract Background Recently, International Diabetes Federation position statement has adopted one-hour post-load glucose (1hPG) ≥ 8.6 mmol/L for diagnosing intermediate hyperglycemia. We aimed to assess the association of 1hPG ≥ 8.6 mmol/L with metabolic syndrome (MetS) and its components, as well as interaction between sex and 1hPG ≥ 8.6 mmol/L on MetS and its components in Chinese people at high risk of diabetes. Methods The cross-sectional study was conducted in DaQing city of HeiLongJiang Province, China between August, 2023 and January, 2024. Eligible individuals with fasting glucose of 5.6–6.9 mmol/L and age of 25–55 years in health checkup data in the year of 2023 or with at least one risk factor of diabetes were invited to receive the oral glucose tolerance test and biochemical examinations. Individuals with self-reported presence of diabetes or usage of glucose-lowering medication were excluded. MetS was defined as presence of at least three of the five components according to the Chinese Diabetes Society criteria. Logistic regression was performed to evaluate the association of 1hPG ≥ 8.6 mmol/L with MetS and its components. Additive interaction was estimated using the relative excess risk due to interaction, attributable proportion due to interaction (AP), and synergy index. Results A total of 2419 subjects comprising 1465 men (60.6%) with a mean age of 45.77 ± 6.20 years were included, and the prevalence of MetS was 46.8%, with 59.7% in men and 27.1% in women. 1hPG ≥ 8.6 mmol/L was associated with MetS (aOR = 4.40, 95% CI 3.26–6.01), elevated blood pressure (aOR = 1.46, 95% CI 1.13–1.89), hyperglycemia (aOR = 15.46, 95% CI 11.56–20.98), and reduced HDL-C (aOR = 1.51, 95% CI 1.07–2.15) in the overall population, whereas no significant association between 1hPG ≥ 8.6 mmol/L and elevated blood pressure in men (aOR = 1.36, 95% CI 0.97–1.91) or dyslipidemia in women (elevated TG: aOR = 0.81, 95% CI 0.47–1.39; reduced HDL-C: aOR = 1.08, 95% CI 0.49–2.37). Additive interaction effect between sex and 1hPG ≥ 8.6 mmol/L on MetS was observed, with 31% attributed to the interaction effect between men and 1hPG ≥ 8.6 mmol/L (AP = 0.31, 95% CI 0.06–0.49). Conclusions There was an additive interaction effect between sex and 1hPG on MetS among Chinese people at high risk of diabetes. 1hPG test and sex-specific strategies should be taken into consideration in cardiometabolic disorder identification and management.